2005
DOI: 10.1007/bf03016069
|View full text |Cite
|
Sign up to set email alerts
|

Management following resuscitation from cardiac arrest: Recommendations from the 2003 Rocky mountain critical care conference

Abstract: P Pu ur rp po os se e: : To propose a strategy for the management of patients admitted to critical care units after resuscitation from cardiac arrest.S So ou ur rc ce e: : Prior to the conference relevant studies were identified via literature searches and brief reviews circulated on the following topics: glucose and blood pressure management; therapeutic hypothermia; prearrest outcome prediction; post-arrest outcome prediction; and management of myocardial ischemia. Two days were devoted to assessing evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 113 publications
0
20
0
1
Order By: Relevance
“…The time frame for the search has been from August 1961 to May 2009. Grading of evidence and grading of recommendations were performed according to a system first used by Bell et al 1 Table 2. According to this system, evidence is graded from A to E, where recommendation grade A indicates a recommendation based on the best evidence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time frame for the search has been from August 1961 to May 2009. Grading of evidence and grading of recommendations were performed according to a system first used by Bell et al 1 Table 2. According to this system, evidence is graded from A to E, where recommendation grade A indicates a recommendation based on the best evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it is also recommended to use an opioid to reduce the haemodynamic response to tracheal intubation. Grading of evidence from I to V according to Bell et al 1 can be found in the text, added in brackets. Graded recommendations for the choice of hypnotics and opioids can be found in Table 7.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated that a MAP of greater than 65 mm Hg, which may support adequate coronary perfusion, probably is not sufficient to provide adequate blood supply to the brain, unless other therapies that are designed to decrease cerebral metabolic demand are implemented (eg, sedation, hypothermia) [108]. A MAP of 80 to 100 mm Hg has been suggested to be beneficial, at least for the first 24 hours after arrest [109].…”
Section: Cerebral Perfusionmentioning
confidence: 99%
“…However, larger trials are warranted to assess the advantage of early vs. late cooling in humans. It is worth noting that although it took 8 h to reach the target temperature in the HACA trial, there was still a beneficial effect on cerebral out- come and death compared with normothermic patients 21 (GOE I). The optimal duration of therapeutic hypothermia is undetermined.…”
Section: When and For How Long?mentioning
confidence: 99%